Representation of Maximums in Axiolinguistic Evaluation of Politeness Category in Uzbek and English Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the positive and negative evaluation from the axiological aspect of the politeness category in English and Uzbek languages is analyzed with the help of examples taken from fiction literature.